The Effect of Magnitude and Direction of Heat Flow on the Thermal Conductivity for Insulation Materials (Glass Wool) by Using Probe Method - Humaish, Hussein; ., . (International Journal of Engineering and Technology, 2018)
The thermal energy of building is determined by the thermal properties of the materials and how to install these materials in the elements of buildings according to the direction of heat transfer. The effectiveness of thermal insulation (glass wool) is dependent on its thermal conductivity which is varies in different directions of fibers of glass wool. Glass wool is formed of fibers and binders tangled together during the industrial process to provide some elasticity. The experimental values of thermal conductivity of the insulation materials are changed according to magnitude of the heat power and direction of fiber arrangement. The thermal conductivity for insulation materials has been measured by using probe method,Â Huekseflux Â® TP02 used to measure the thermal conductivity by emit the flow perpendicular and parallel to the fibers of glass wool. Two samples of yellow glass wool (density 68 kg/m3) with dimensions (10 Ã—10 Ã—30) cm have been used. Hot Disk bulk isotropic module has been used to evaluate thermal conductivity. TPS source (Hot Disk probe reference: 4922) characterized by a diameter of 14.61 mm has been selected. COMSOLÂ® multiphysics axisymmetric 2D model has been used to follow the axial and the radial directions of the heat transfer.Â